Bergamosoma canestrinii - Kime, Richard Desmond; Enghoff, Henrik (Zenodo, 2021)
185. Bergamosoma canestrinii (Fedrizzi, 1877) Fig. 1E Megalosoma canestrinii Fedrizzi, 1877. Prionosoma baldense Verhoeff, 1934. Atractosoma canestrinii auct. Craspedosoma canestrinii auct. Prionosoma canestrinii auct. Distribution AT, CH, DE, IT-ITA. Habitat Rocky areas with shallow soil, alpine meadows with Dryas octopetala L. on south-facing slopes. Also subalpine, strictly calcicole and found from 1000–2460 m a.s.l. in Switzerland. Occasionally in caves, once in a botanic garden. Remarks Found feeding on fox ( Vulpes vulpes (Linnaeus, 1758)) excrements in the Swiss National Park (J.D. Gilgado pers. com., see Fig. 1E). Published as part of Kime, Richard Desmond & Enghoff, Henrik, 2021, Atlas of European millipedes 3: Order Chordeumatida (Class Diplopoda), pp. 1-244 in European Journal of Taxonomy 769 on page 66, DOI:10.5852/ejt.2021.769.1497, http://zenodo.org/record/5536353